Performance analysis of Fe–N–C catalyst for DMFC cathodes: Effect of water saturation in the cathodic catalyst layer - Monteverde Videla, Alessandro H.A.; Sebastián, David; Vasile, Nicolo S.; Osmieri, Luigi; Aricò, Antonino S.; Baglio, Vincenzo; Specchia, Stefania (International journal of hydrogen energy, 2016)
Iron phthalocyanine (FePc) was used as iron/nitrogen/carbon source and templated with an ordered mesoporous silica (SBA-15), followed by heat treatment and leaching of SiO2 with hydrofluoric acid (sacrificial method). The Fe–N–C catalyst was tested for the oxygen reduction reaction using a rotating disk electrode (three electrode configuration) in the presence of methanol at different concentrations. Furthermore, the catalyst was investigated in a single cell configuration of a direct methanol fuel cell (DMFC) under different methanol concentrations and temperatures. The optimal operating condition was found to be 1 M at 110 °C, reaching 11.2 mW cm−2 using a commercial Pt-Ru black at the anode and the Fe–N–C at the cathode side. Interestingly, the cathodic catalyst was not dramatically affected by the presence of crossovered methanol, showing only a 12% drop in maximum power density with the highest methanol concentration of 10 M at the anode. A 3D multiphysics model was implemented to further explain the experimental DMFC performance data using a commercial platform (Comsol® Multiphysics v4.4a). The model agreed with the experimental data, showing a direct relationship between water saturation, and oxygen consumption, consequently oxygen starvation at the cathodic catalytic layer. The model considered two phases on the cathode side computed by extended Darcy law within the catalytic layer and the gas diffusion layer domains. [Display omitted] •Fe–N–C catalyst for ORR synthesized using Fe-phthalocyanine and SBA-15 silica.•Highly methanol tolerant ORR catalyst up to 10 M methanol concentration.•3D multi-physic model of GDE for ORR computed by Comsol® v4.4a platform.•Model validated against experimental data of Fe–N–C as cathode on single cell DMFC.•Oxygen partial pressure distribution affects flooding and, thus, DMFC performance.